Covid-19 Pandemic; Interest In Entrepreneurship And Competency Development Of Micro, Small And Medium Entrepreneurs In Surabaya - Asmirin Noor; Tri Cicik Wijayanti; Shenna Zenitha Afdhally; Dewi Suprihandari (Asian Journal of Management, Entrepreneurship and Social Science, 2021)
This study aims to determine the effect of the Covid-19 Pandemic on Interest in Entrepreneurship and on Increasing the Entrepreneurial Capability of MSMEs in the City of Surabaya. The research approach used is a quantitative research using path analysis. The population of this study is the perpetrators of MSMEs in Surabaya, with a total sample of 97 people. Samples were taken using the Convenience Sampling technique. The study results show a positive and significant influence between the COVID-19 pandemic on entrepreneurial interest and entrepreneurial Competence, as well as a positive and significant influence between entrepreneurial interest on increasing the entrepreneurial Competence of MSME actors in the city of Surabaya